BANYUWANGI ETHNO CARNIVAL (BEC) STUDIES ON POP CULTURE AND TRADITIONAL CULTURE - Fauziah Ali; Imro'atul Husna Afriani; St. Shabibatul Rohmah; Mahfud (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Banyuwangi Ethno Carnival (BEC) is a program of the Banyuwangi Regency government which aims to introduce the culture of the people of Banyuwangi as well as an effort to increase regional income. By carrying out its ethnic elements, the Banyuwangi Government hopes that this can attract the interest of tourists who will visit Banyuwangi Regency. This research examines how the process of traditional culture at the Banyuwangi Ethno Carnival (BEC) event becomes pop culture that is popular with the community. In this study, researchers used a qualitative description with a literature study approach. The results of this study indicate that: a. Based on socio-cultural factors, The Banyuwangi government carries ethnic values ​​contained in Banyuwangi culture with the aim of being able to introduce Banyuwangi culture to the outside world; b. Based on economic factors, this event is able to become an alternative to level the wheels of the economy in Banyuwangi Regency to grow rapidly, so that many investors are looking and investing in this event; and c. Based on political factors, the Banyuwangi Ethno Carnival (BEC) and stakeholders are involved together and have collaborated since the planning, funding and implementation of the Banyuwangi Ethno Carnival (BEC) program. so that many investors glance and invest in this event; and c. Based on political factors, the Banyuwangi Ethno Carnival (BEC) and stakeholders are involved together and have collaborated since the planning, funding and implementation of the Banyuwangi Ethno Carnival (BEC) program. so that many investors glance and invest in this event; and c. Based on political factors, the Banyuwangi Ethno Carnival (BEC) and stakeholders are involved together and have collaborated since the planning, funding and implementation of the Banyuwangi Ethno Carnival (BEC) program.